The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1037/a0016810
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of 4-year college student performance using cognitive and noncognitive predictors and the impact on demographic status of admitted students.

Abstract: This study was conducted to determine the validity of noncognitive and cognitive predictors of the performance of college students at the end of their 4th year in college. Results indicate that the primary predictors of cumulative college grade point average (GPA) were Scholastic Assessment Test/American College Testing Assessment (SAT/ACT) scores and high school GPA (HSGPA) though biographical data and situational judgment measures added incrementally to this prediction. SAT/ACT scores and HSGPA were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(126 citation statements)
references
References 60 publications
(80 reference statements)
3
119
1
2
Order By: Relevance
“…The predictive values of aptitude tests and HSGPA for academic achievement in universities have been well verified in the United States (e.g., Geiser & Santelices, 2007;Schmitt et al, 2009;Sackett, Kuncel, Arneson, Cooper, & Waters, 2009). In Finland, while universities can decide their student admission criteria independently, matriculation examination grades and/or entrance examinations are the most commonly used.…”
Section: Critical Thinking and Academic Achievementmentioning
confidence: 99%
“…The predictive values of aptitude tests and HSGPA for academic achievement in universities have been well verified in the United States (e.g., Geiser & Santelices, 2007;Schmitt et al, 2009;Sackett, Kuncel, Arneson, Cooper, & Waters, 2009). In Finland, while universities can decide their student admission criteria independently, matriculation examination grades and/or entrance examinations are the most commonly used.…”
Section: Critical Thinking and Academic Achievementmentioning
confidence: 99%
“…Additionally, the non-cognitive factor of persistence suggested that an individuals' perseverance accounted for successful educational retention (Duckworth, Peterson, Matthews, & Kelly, 2007). Schmitt et al (2009) demonstrated that non-cognitive measures incrementally increase the assessment accuracy of freshman students' academic preparedness during college admission when added to standard cognitive tests. Non-cognitive factors related to intrinsic motivation have a positive association with academic persistence (Kaufman & Dodge, 2009).…”
Section: Non-cognitive Assessmentsmentioning
confidence: 99%
“…Schmitt, et al (2009) conducted a study in which non-cognitive assessments were used to augment the Scholastic Achievement Test (SAT) assessment. Boylan (2009) incorporated non-cognitive (i.e., affective & personal) factors with cognitive factors to develop targeted interventions for underprepared students.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations